Dynamic changes of the ethylene biosynthesis in 'Jonagold' apple. Issue 2 (13th September 2013) - Bulens, Inge; Van de Poel, Bram; Hertog, Maarten L. A. T. M.; Cristescu, Simona M.; Harren, Frans J. M.; De Proft, Maurice P.; Geeraerd, Annemie H.; Nicolai, Bart M.
<x xml:space="preserve">Abstract</x> In this study, the short‐term and dynamic changes of the ethylene biosynthesis of Jonagold apple during and after application of controlled atmosphere (CA) storage conditions were quantified using a systems biology approach. Rapid responses to imposed temperature and atmospheric conditions were captured by continuous online photoacoustic ethylene measurements. Discrete destructive sampling was done to understand observed changes of ethylene biosynthesis at the transcriptional, translational and metabolic level. Application of the ethylene inhibitor 1‐methylcyclopropene (1‐MCP) allowed for the discrimination between ethylene‐mediated changes and ethylene‐independent changes related to the imposed conditions. Online ethylene measurements showed fast and slower responses during and after application of CA conditions. The changes in 1‐aminocyclopropane‐1‐carboxylate synthase (ACS) activity were most correlated with changes in ACS1 expression and regulated the cold‐induced increase in ethylene production during the early chilling phase. Transcription of ACS3 was found ethylene independent and was triggered upon warming of CA‐stored apples. Increased expression of ACO1 during shelf life led to a strong increase in 1‐aminocyclopropane‐1‐carboxylate oxidase (ACO) activity, required for the exponential production of ethylene during system 2. Expression of ACO2 and ACO3 was upregulated in 1‐MCP‐treated fruit showing a negative correlation with ethylene production. ACO activity never became rate limiting.